DEVELOPMENT OF PNEUMATIC LAUNCHER - P S, Shri Harish; G, Navaneeth Krishnan; M, Venkat Prashanth (IJRDO - Journal of Mechanical And Civil Engineering, 2018)
Compressed air is used to propel a grenade from a closed cavity. Pressure change in a closed environment will result in propelling of object from the closed chamber. The pneumatic source can be stored in a chamber for portability and even a live source can be directly connected to the gun. The grenade will accelerate with the compressed air, when the air is trying to escape into the low-pressure atmosphere air. The acceleration of the grenade depends upon the pressure of the air and higher pressure will generate more acceleration. Inside the closed chamber if the air is supplied through a small opening and if an attachment is being attached to the opening then the pressure created will be less and the grenade will start rotating inside the chamber. To overcome this, that attachment should not be attached with the opening it should be placed over a very small distance from the gun, so that a vacuum will be produced from the atmosphere and the grenade could be launched at a high pressure.